From Bacteria to Bach and Back : The Evolution of Minds - Daniel C. Dennett (Allen Lane, an imprint of Penguin Books, 2017)
'Required reading for anyone remotely curious about how they came to be remotely curious' Observer'Enthralling' Spectator What is human consciousness and how is it possible? These questions fascinate thinking people from poets and painters to physicists, psychologists, and philosophers. This is Daniel C. Dennett's brilliant answer, extending perspectives from his earlier work in surprising directions, exploring the deep interactions of evolution, brains and human culture. Part philosophical whodunnit, part bold scientific conjecture, this landmark work enlarges themes that have sustained Dennett's career at the forefront of philosophical thought. In his inimitable style, laced with wit and thought experiments, Dennett shows how culture enables reflection by installing a profusion of thinking tools, or memes, in our brains, and how language turbocharges this process. The result: a mind that can comprehend the questions it poses, has emerged from a process of cultural evolution. An agenda-setting book for a new generation of philosophers and thinkers, From Bacteria to Bach and Back is essential for anyone who hopes to understand human creativity in all its applications